EVALUASI EFEKTIVITAS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DI SMKS YOHANES XXIII MAUMERE - Chrisantus Aderay Boruk; Andreas Rengga; Kristiana Reinaldis Aek (Universitas Nusa Nipa Maumere, 2026)
This research aimed to evaluate the effectiveness of the management of School Operational Assistance Funds at SMKS Yohanes XXIII Maumere. The management of School Operational Assistance Funds is an important aspect in supporting the smooth implementation of the learning process and improving the quality of education. The research used a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results indicated that the management of School Operational Assistance Funds at SMKS Yohanes XXIII Maumere has been implemented following the applicable technical guidelines and adheres to the principles of transparency, accountability, efficiency, and effectiveness. The School Operational Assistance Funds were utilized to support the eight national education standards, particularly in the development of facilities and infrastructure, process standards, and school operational financing. However, there were still challenges in the form of delays in fund disbursement, which affect the optimal implementation of school programs. Overall, the management of School Operational Assistance Funds at SMKS Yohanes XXIII Maumere can be categorized as effective. Nevertheless, improvements were needed in the aspects of planning and fund disbursement time management to ensure that the benefits of School Operational Assistance Funds can be maximized.